Transnational geographies of the heart : intimate subjectivities in a globalising city - Walsh, Katie (Hoboken, NJ : John Wiley & Sons, Ltd, 2018)
Transnational Geographies of the Heart explores the spatialisation of intimacy in everyday life through an analysis of intimate subjectivities in transnational spaces. The author draws on ethnographic research with British migrants in Dubai, United Arab Emirates, during a phase of rapid globalisation and economic diversification in 2002-2004. This research highlighted the negotiation of inter-personal relationships as enormously significant in relation to the dialectic of home and migration. A range of relationships are discussed in four empirical chapters focused on the production of'expatriate' subjectivities, community and friendships, sex and romance, and families. The British migrants interviewed are diverse in terms of their length of residence, occupation, age, gender and marital status yet, at the same time, their reproduction of middle class, white and heteronormative subjectivities in postcolonial space marks them as privileged in collective terms. Essential reading for geographers, sociologists and anthropologists, this book demonstrates that a critical analysis of the geographies of intimacy might productively contribute to our understanding of the ways in which intimate subjectivities are embodied, emplaced, and co-produced across binaries of public/private and local/global space. --Book Jacket.
'Family Time' and Space for FamilyGlobal Work, Expatriation and Marriage; Adult Children and the Family Home; Transnational Connections and Family'Left Behind'; Conclusion; Chapter Eight Our Intimate Lives; Exploring the Spatialisation of Intimacy; Changing Gulf Subjectivities: Temporalities of Intimacy; Intimacy, Belonging and Home: Rethinking the Global City; References; Index; EULA.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on May 24, 2018).
Keywords: British -- United Arab Emirates -- Social life and customs; Interpersonal relations; Aliens -- United Arab Emirates; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Aliens; British -- Social life and customs; Interpersonal relations; United Arab Emirates; Electronic books